Comment on hawking radiation, unruh radiation, and the equivalence principle - Crispino, Luís C. B.; Higuchi, Atsushi; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2012)
A Comment on the Letter by Douglas Singleton and Steve Wilburn, Phys. Rev. Lett.PRLTAO0031-9007 107, 081102 (2011)10.1103/PhysRevLett.107.081102. The authors of the Letter offer a Reply. © 2012 American Physical Society.